Antenatal diagnosis and treatment of hypothyroid fetal goiter in an euthyroid mother: a case report and review of literature. (12th December 2015) - Mastrolia, Salvatore Andrea; Mandola, Amarilla; Mazor, Moshe; Hershkovitz, Reli; Mesner, Oded; Beer-Weisel, Ruthy; Besser, Limor; Shelef, Ilan; Loewenthal, Neta; Golan, Agneta; Gruzman, Igor; Erez, Offer
Abstract: Fetal goiter is an extremely rare complication of pregnancy. Its incidence is 1 in 40 000 deliveries. Antithyroid maternal therapy is responsible for 10–15% of fetal congenital hypothyroidism and can be considered as the most frequent underlying cause for this condition. The frequency of fetal goiter that is associated with fetal hypothyroidism and normal maternal thyroid function, as in our case, is even less frequent. Fetal goiter is associated with increased rate of perinatal complications and long-term morbidity, due to peripartum complications including labor dystocia due to its mass effect, as well as neonatal airway obstruction that may lead to hypoxic-ischemic brain injury and death. We present, in this study, a case report of late antenatal fetal goiter in an euthyroid woman and a literature review of the diagnosis and treatment of these cases.